Immediate deep vein thrombosis after trauma: Case report - Majid Zamani; Farhad Heidari; Elahe Nasri Nasrabadi (Trauma Case Reports)
Considering that the diagnostic time of DVT after trauma and the risk factors associated with its incidence as well as its preventive and therapeutic management are very significant, the present study reported a rare case with acute DVT occurring in the shortest time after trauma. This patient was a 19-year-old man who was taken to the hospital due to a motorcycle and car accident. Despite the normality of the clinical examinations and lack of any fractures in the lower and upper limbs, the patients experienced sudden pain and swelling of the left leg in about 6 h after trauma. The venous color Doppler ultrasound showed that SFV, CFV, popliteal veins, and the saphenofemoral junction had no flow and were non-compressible. Therefore, the patient was treated with anticoagulant following the diagnosis of acute DVT. After 10 days of treatment, he was discharged with anticoagulant drug.